2004
DOI: 10.1038/nature02550
|View full text |Cite|
|
Sign up to set email alerts
|

Iron and phosphorus co-limit nitrogen fixation in the eastern tropical North Atlantic

Abstract: The role of iron in enhancing phytoplankton productivity in high nutrient, low chlorophyll oceanic regions was demonstrated first through iron-addition bioassay experiments and subsequently confirmed by large-scale iron fertilization experiments. Iron supply has been hypothesized to limit nitrogen fixation and hence oceanic primary productivity on geological timescales, providing an alternative to phosphorus as the ultimate limiting nutrient. Oceanographic observations have been interpreted both to confirm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

48
794
3
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 889 publications
(853 citation statements)
references
References 30 publications
48
794
3
8
Order By: Relevance
“…In the subtropical western North Atlantic, the strong seasonal cycle in P flux results in a large variation in the N/P ratios in deposition, with up to an eightfold difference in the interannual seasonal ratios and lower ratios during the summer months. The seasonal variation in P deposition may have important biological implications; for example, via the stimulation of N 2 fixation [Mills et al, 2004], although further biological studies are needed to more fully assess the bioavailability of atmospheric-derived P.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the subtropical western North Atlantic, the strong seasonal cycle in P flux results in a large variation in the N/P ratios in deposition, with up to an eightfold difference in the interannual seasonal ratios and lower ratios during the summer months. The seasonal variation in P deposition may have important biological implications; for example, via the stimulation of N 2 fixation [Mills et al, 2004], although further biological studies are needed to more fully assess the bioavailability of atmospheric-derived P.…”
Section: Discussionmentioning
confidence: 99%
“…Selective removal of P from dissolved organic matter [Clark et al, 1998] and high N/P ratios of nutrients in the main thermocline [Ammerman et al, 2003;Fanning, 1992] are also observed. In some organisms, particularly diazotrophs, P is even thought to be limiting or colimiting growth [Mills et al, 2004;Moore et al, 2008;Sañudo-Wilhelmy et al, 2004].…”
Section: Introductionmentioning
confidence: 99%
“…The best current information on the environmental factors controlling N 2 -fixation in the Atlantic comes from an elaborate set of bioassay experiments carried out by Mills et al (2004) on Cruise ME55. These experiments were designed to explore the role of iron and phosphorus in limiting N 2 fixation in surface waters of the Eastern Tropical Atlantic.…”
Section: Implications and Conclusionmentioning
confidence: 99%
“…The dynamics of the ocean and its interaction with the atmosphere are strongly linked to the properties of seawater. Elements such as Fe limit marine primary production in half of the world ocean (Moore et al 2001) and thus may have a profound effect on plankton communities and the global carbon cycle (Martin and Fitzwater 1988; Mills et al 2004). More reliable determinations of micronutrient elements in marine waters are thus essential to enhance our understanding of their impact on ocean productivity and processes (e.g., ocean acidification).…”
mentioning
confidence: 99%